Rapid rotational grazing as best-bet option to control endoparasites - Cruz, E.M.; Barcelo, P.M.; Ancheta, P.B.; Fontanilla, P.; Camalia, F.M.; Ancheta, V.G.; Gray, G.D.; Villar, E.C. (Philippine Society of Animal Science, 2000)
In the Philippines, management of grazing flock like rotational grazing is not being done as a parasite control, but to improve the condition of the pasture and the nutritional status of the animals. Posas (1981) compared goat production and impact of soil, pasture, and coconut production. Rotational grazing was practiced and Reported that confined animals grew less than grazing animals in terms of gain/ha./year. Guss (1983) argued that grazing goats in the tropics may not be successful, thereof it could be necessary to resort to a totally confined system in a simple inexpensive housing on slatted floors has helped control internal parasite. Likewise, the separation of the age groups as a management procedure to reduce the transmission and spread of parasites is not practiced. Rotational grazing is a process of moving the animals to another pasture just before the infective larval stage are likely to appear in significant numbers on the original pasture. It is an evasive process since the pasture areas should not be grazed during the Development of the parasite into infective stages. This study was conducted to determine the effectivity of rapid rotational grazing in controlling endoparasites in goats. Specifically, it aims to determine the parasitic load (FEC), gain in weight and packed cell volume (PCV) of the experimental animals.